Data synchronization by continuous spatial measurement with Double Ballbar. (April 2021) - Zhou, Ruiqing; Kauschinger, Bernd; Ihlenfeldt, Steffen
Abstract: In this paper, we first present the continuous spatial Double Ballbar (DBB) measurement we purposed in our former work and then suggest two possible solutions to determine the correspondence of the actual machine poses to the DDB measuring values, so as to extend the scope of application of the continuous spatial DBB measuring approach to quantitative tasks such as calibration. For the machines, on which integrated capture of both data is not possible, it is more flexible to capture the data simultaneously in separate devices and adjust them thereafter. We address the issues of asynchrony and inhomogeneity arising therefrom and purpose an approach which could be automated and integrated as a preprocessing module into the data processing program for further use. The technical feasibility of the data capture concept, along with the purposed approach to synchronization and homogenization, was experimentally validated through measurement on a Stewart–Gough platform controlled using Beckoff TwinCAT. Highlights: Analysis of asynchrony and inhomogeneity by continuous spatial DBB measurement. Approach to aligning separately captured machine data and measuring value. Improvement on flexibility of continuous DBB measurement for quantitative tasks.